2008
DOI: 10.1103/physrevlett.100.197401
|View full text |Cite
|
Sign up to set email alerts
|

Fast Optical Preparation, Control, and Readout of a Single Quantum Dot Spin

Abstract: We propose and demonstrate the sequential initialization, optical control, and readout of a single spin trapped in a semiconductor quantum dot. Hole spin preparation is achieved through ionization of a resonantly excited electron-hole pair. Optical control is observed as a coherent Rabi rotation between the hole and charged-exciton states, which is conditional on the initial hole spin state. The spin-selective creation of the charged exciton provides a photocurrent readout of the hole spin state. DOI: 10.1103/… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
150
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(153 citation statements)
references
References 26 publications
2
150
0
1
Order By: Relevance
“…The initialization in the Voigt configuration is three orders of magnitude quicker than in the Faraday configuration, but the fidelity of this latter configuration is greater. Recently, in absence of an applied magnetic field, Ramsay et al 47 have demonstrated the sequential hole-spin initialization by the ionization of a spin-polarized electron-hole pair with an 81% fidelity, and Gerardot et al 13 have also obtained a high fidelity of the spin state initialization for a single hole under cw optical excitation. In the past, Shabaev et al 48 have proposed the initialization of a single electron spin placed in a transverse magnetic field by a combination of circularly polarized optical π pulses, and the authors have predicted a spin polarization of 99% after eight pulses.…”
Section: Discussionmentioning
confidence: 99%
“…The initialization in the Voigt configuration is three orders of magnitude quicker than in the Faraday configuration, but the fidelity of this latter configuration is greater. Recently, in absence of an applied magnetic field, Ramsay et al 47 have demonstrated the sequential hole-spin initialization by the ionization of a spin-polarized electron-hole pair with an 81% fidelity, and Gerardot et al 13 have also obtained a high fidelity of the spin state initialization for a single hole under cw optical excitation. In the past, Shabaev et al 48 have proposed the initialization of a single electron spin placed in a transverse magnetic field by a combination of circularly polarized optical π pulses, and the authors have predicted a spin polarization of 99% after eight pulses.…”
Section: Discussionmentioning
confidence: 99%
“…Recent results have demonstrated marked progresses towards realization of fast optical manipulation of single spins in QDs (Ref. 8) and optically effected controlled-phase gate between two solid-state qubits. 9 One way of achieving spin polarized carriers and excitons in QDs is via direct spin injection from an adjacent layer.…”
mentioning
confidence: 99%
“…Continuous-wave pumping schemes for the high-fidelity preparation of an electron [20], and hole [21] spin have been demonstrated, not only in a Faraday geometry B-field, but also for electron spins in the Voigt geometry B-field needed for optical control [22,23]. Recently, partial [24,25], and full [26] optical control of a single electron spin has been demonstrated. Full optical control of a single spin is achieved when both the occupation, and relative phase of the spin states can be fully controlled, or in other words, from a well defined initial state, any arbitrary spin state can be prepared.…”
Section: Introductionmentioning
confidence: 99%
“…In this article, we propose and demonstrate the sequential optical preparation, control, and detection of a single hole spin trapped on an InGaAs/GaAs quantum dot [25]. Using a dot embedded in an n-i-Schottky diode structure, hole spin initialization is achieved by creating a spin-polarized electron-hole pair with near unit probability using a picosecond laser pulse with a pulsearea of π, and waiting for the electron to tunnel leaving a spin-polarized hole.…”
Section: Introductionmentioning
confidence: 99%